Elipse Horizontal - Solís-Palma, Angie (My University, 2017)
Applet realizado en GeoGebra. Manipule los valores del centro y los valores que generan el eje mayor y menor. Observe la ecuación canónica, características y la gráfica de la elipse que se obtiene.

Applet made in GeoGebra. Manipulate the center values ​​and the values ​​that generate the major and minor axis. Look at the canonical equation, characteristics and the graph of the ellipse you get.
Keywords: GeoGebra; Secciones cónicas; Conic sections; Cálculo de variables; Variable calculation; Elipse; Ellipse; Calculus; Applet